The Effect of Hydroxyapatite Filling from Chicken Eggshells in the Formulation of Brown Algae (Sargassum sp.) Extract on Setting Time - Kadek Ayu Wirayuni; Tri Purnami Dewi; Ria Koesoemawati; Pande Luh Gede Lenny Wulandari (Interdental Jurnal Kedokteran Gigi (IJKG), 2024)
Introduction: Alginate is often chosen in the impression process because it’s easy to use, has good accuracy, easy to modify, and is comfortable for the patient. Alginate's setting time can be manipulated by adding calcium phosphate or calcium sulfate. Hydroxyapatite (HA) is a calcium phosphate compound and member of the apatite group of minerals. Material and Methods: The experimental design of this study was Post Test Only Control Group Design with 21 total samples and consisting of 3 treatment groups. Treatment groups P1 and P2 with hydroxyapatite filling as much as 5 g and 7 g. Positive control group using Aroma Fine Plus® fast setting impression material. Setting time is measured using a stopwatch. Results and Discussions: The results showed that the average setting time produced by the KP, P1 and P2 groups respectively was 1 minute 13 seconds, 2 hours 1 minute 27 seconds, and 2 hours 45 minutes 2 seconds. Analysis with Shapiro-Wilk Test and Levene's Test showed that the data was normally distributed and homogeneous. Data analysis with One Way ANOVA test showed a significance of <0.05, which means that there is a significant difference in the average setting time results. The Post Hoc LSD test showed a significance of <0.05 in all treatment groups indicating that there were significant differences between groups. Conclusion: It can be concluded from the results of this study is that the hydroxyapatite filling of chicken egg shells in the brown algae extract formulation (Sargassum sp.) did not affect the setting time acceleration.